Cognitive sociolinguistics revisited - Kristiansen, Gitte 1966-; Franco, Karlien; De Pascale, Stefano; Rosseel, Laura; Zhang, Weiwei (De Gruyter Mouton, 2021)
Cognitive Sociolinguistics draws on the rich theoretical framework of Cognitive Linguistics and focuses on the social factors that underlie the variability of meaning and conceptualization. In the last decade, the field has expanded in various way. The current volume takes stock of current and emerging advances in the field in short academic contributions. The studies collected in this book have a usage-based approach to language variation and change, drawing on the theoretical framework of Cognitive Linguistics and are sensitive to social variation, be it cross-linguistic or language-internal. Three types of contributions are collected in this book. First, it contains theoretical overview papers on the domains that have witnessed expansion in recent years. Second, it presents novel research ideas in proof-of-concept contributions, aimed at blue-sky research and out-of-the-box linguistic analyses. Third, it showcases recent empirical studies within the field. By combining these three types of contributions, the book provides an encompassing overview of novel developments in the field of Cognitive Sociolinguistics
Keywords: LANGUAGE ARTS & DISCIPLINES / Linguistics / General / bisacsh; Soziolinguistik; Kognitive Linguistik; Aufsatzsammlung